Enhancing motivation by developing cyclical self-regulated learning skills. Issue 1 (2nd January 2022) - Callan, Gregory L.; DaVia Rubenstein, Lisa; Barton, Tyler; Halterman, Aliya
ABSTRACT: Developing self-regulated learning (SRL) processes (i.e., goal-setting, strategy use, self-monitoring, and attributions) can enhance motivational beliefs including self-efficacy, interest, and task value. In this article, SRL processes and motivation are conceptualized within a cyclical feedback loop, which demonstrates how SRL processes affect motivation for both current and future tasks. Thus, educators can directly teach SRL processes to improve motivation using feasible classroom-based practices and resources.